Analisa Pelaksanaan Tax Amnesty Di Indonesia - Ni Kadek Ayu Mega Sri Deviani Putri; Kyara Dewanti Maheswari (Universitas Pendidikan Ganesha, 2021)
The most inland revenue financed by taxes, especially the state of Indonesia. In increasing state revenue, it can be done by implementing tax amnesty or it’s called tax amnesty.the purpose of this study is to see the influence of knowledge and understanding of the tax amnesty, and to see analysis of the implementation of tax amnesty for three periods. Data analysis technique used is descriptive technique. The results of this study shows that the knowledge and understanding of tax amnesty, and to see analysis of the implementation of tax amnesty for three periods.